2x+13=-5x-7x

Simple and best practice solution for 2x+13=-5x-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+13=-5x-7x equation:


Simplifying
2x + 13 = -5x + -7x

Reorder the terms:
13 + 2x = -5x + -7x

Combine like terms: -5x + -7x = -12x
13 + 2x = -12x

Solving
13 + 2x = -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
13 + 2x + 12x = -12x + 12x

Combine like terms: 2x + 12x = 14x
13 + 14x = -12x + 12x

Combine like terms: -12x + 12x = 0
13 + 14x = 0

Add '-13' to each side of the equation.
13 + -13 + 14x = 0 + -13

Combine like terms: 13 + -13 = 0
0 + 14x = 0 + -13
14x = 0 + -13

Combine like terms: 0 + -13 = -13
14x = -13

Divide each side by '14'.
x = -0.9285714286

Simplifying
x = -0.9285714286

See similar equations:

| 18a/6 | | (7+5i)+(5i)= | | (x-2x/100)*60/100*70/100=7203 | | (5x+11)=360 | | (-8i)-(3i)= | | 4d=1/3 | | x+(3x+15)=135 | | 256x^2=-176 | | Y+5-6y=17-2y | | 1.2c=0.6 | | (3i)-(I)= | | 3d+5d+9d-8= | | f(x)=6x^3+11x^2-10x | | (8j-9)=14 | | 6=3/5w | | 4(d+3)= | | 2w-3=2w | | a+5a+4b= | | 1.6x=2.5y+2 | | 7v/6=42 | | 7+9x=180 | | 9*x^2+3*x-2=0 | | 17+4x=180 | | -2x+3x=-52+13x | | m-33=-3.19 | | x+90+x+3=180 | | (72-x)+(4x+32)=180 | | d^4-3d^3-2d^2+2d+2=0 | | 11-(2x+3)=-2x-8 | | 2r^2(r^2+5r+4)=0 | | m/2.3=-3 | | m/2.3= |

Equations solver categories